Building a Technopark through Collaboration and Innovation with Pentahelix Model - Mariam, Iis; Latianingsih, Nining; Wartiningsih, Endah; Sofa, Nidia; Fiana, Putri (Standards-related Regional Innovation and International Cooperation, 2025)
This research examines the role of technoparks in Indonesia as innovation ecosystems that bridge academia and industry through Collaborative Knowledge Creation and the Pentahelix model. While technoparks are designed to integrate research, business, and government support, persistent challenges limit their effectiveness, including bureaucratic delays in Memorandum of Understanding/Memorandum of Action processes, inconsistent funding, and uneven industrial commitment, where partnerships are often perceived merely as corporate social responsibility. Using Soft Systems Methodology, this research analyzes data from several institutions. The findings highlight systemic misalignments between conceptual models and real practices, underscoring the need for reforms in policy, incubation, and dissemination mechanisms. Systematically desirable and culturally feasible changes include streamlining cooperation procedures, expanding incubation to accelerate commercialization, and strengthening media as a knowledge diffuser. Evidence shows that corrective actions have been initiated through the development of career support, intellectual property management, Small and Medium Enterprises assistance, and entrepreneurship incubation. This research was conducted in three provinces (Aceh, West Sumatra, and West Java). The results show that the presence of technoparks on campus has increased collaboration and cooperation, particularly in Micro, Small, and Medium Enterprises (MSME) business development, which Collaborative Knowledge Creation and Pentahelix concept implemented. The research concludes that embedding Collaborative Knowledge Creation and Pentahelix principles can transform a technopark into an inclusive and sustainable platforms that strengthen competitiveness, entrepreneurial growth, and community empowerment.